Regulation of Chromatin States by Drugs of Abuse - Walker, Deena M (Curr Opin Neurobiol, 2014)
Drug addiction involves long-term behavioral abnormalities and gene expression changes throughout the mesolimbic dopamine system. Epigenetic mechanisms establish/maintain alterations in gene expression in the brain, providing the impetus for investigations characterizing how epigenetic processes mediate the effects of drugs of abuse. This review focuses on evidence that epigenetic events, specifically histone modifications, regulate gene expression changes throughout the reward circuitry. Drugs of abuse induce changes in histone modifications throughout the reward circuitry by altering histone-modifying enzymes, manipulation of which reveals a role for histone modification in addiction-related behaviors. There is a complex interplay between these enzymes, resulting in a histone signature of the addicted phenotype. Insights gained from these studies are key to identifying novel targets for diagnosis and therapy.